Hubungan Anemia pada Kehamilan dengan Berat Badan Bayi Lahir di RSUD Dr. Moewardi - Damara, Novia; Harsono, Ganung; Suryawan, Arif (Nexus Kedokteran Klinik, 2013)
Background: Anemia is a problem in world health which attack a quarter of world population. Pregnancy anemia can caused bad effects to mother or the fetus. This research aims to reveal the relationship between pregnancy anemia and birth weight (high, normal, or low) in RSUD Dr. Moewardi Methods: This study was observational analytic with cross-sectional approach that was conducted in September-October 2012 at the Hospital Dr. Moewardi. The sampling was carried out sampling criterion. The measuring instruments that used were result of laboratory tests in RSUD Dr. Moewardi with cyanmethemoglobin method to determine whether the hemoglobin of pregnant women included in the criteria for anemia and baby scales to measure birth weight. The obtained data were 33 and the data analysis used Chi-Square test with SPSS 17.00 for Windows program. Results: This study demonstrates the value of Chi Square count equal to 33.000, while the value of Chi Square table with Î± = 0.005 and degrees of freedom (df) = 2 obtained a value 5.99. It means that the value of Chi Square count > value of Chi Square table. Meanwhile, with Î± = 0.05 shows p = 0.000, which means that p < 0.05. Thus, the two analyzes are the same conclusions that reject H0. Conclusions: There is a relationship between pregnancy anemia and birth weight in Hospital Dr. Moewardi. The samples were pregnant woman who suffer from mild anemia more likely to deliver babies with normal birth weight. Moreover, woman who suffer from severe anemia more likely to deliver babies with low birth weight. Keywords: Anemia, Pregnancy, Weight Birth